Empowering Female Leadership in Islamic Education: The Role of Decision-Making and Conflict Management in Participatory Governance - Rahmi, Ayatur; Kartiwi, Asti Putri; Connie, Connie; Tamam, Badrud; Aminudin, Aminudin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the influence of decision-making and conflict management skills on the effectiveness of participatory leadership among female State Islamic Junior High School principals in one district in Indonesia with the highest proportion of female principals. The method used was quantitative, ex post facto, with 89 teachers from three Islamic schools as respondents, and the analysis was conducted using multiple regression. The research instrument showed very good validity (r = 0.464–0.952) and high reliability (α = 0.972–0.985). The results showed that decision-making skills had a significant effect on participatory leadership, contributing 82.74% (p < 0.001), while conflict management had a stronger influence, contributing 86.86% (p < 0.001). The two variables simultaneously explained 88.20% of the variation in participatory leadership (F = 322.04, p < 0.001), with conflict management being the dominant predictor (β = 0.64) compared to decision-making (β = 0.32). The implications of this study emphasize the importance of developing madrasah principal training programs that focus on improving conflict management and decision-making competencies, as well as integrating Islamic values, to support educational transformation in madrasas.